Manajemen Pembelajaran Tahfidz di SD Kota Bandung - Mulyani, Reni; Erhamwilda; Huriah Rachmah (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This study aims to analyze the management of Al-Qur’an memorization (tahfidz) learning at a Quran-based elementary school in Bandung City, focusing on the planning, implementation, and evaluation aspects of the program. This research applied a qualitative case study approach, involving the school principal, tahfidz teachers, students, and parents as informants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model with data triangulation. The findings indicate that program planning is carried out through annual meetings with tiered memorization targets for each grade, but the involvement of tahfidz teachers in planning remains limited. The tahfidz learning process utilizes talaqqi, tikrar, and murojaah methods, but faces challenges due to limited facilities and low parental support. Evaluations are conducted daily, monthly, and per semester but have not fully accommodated the diverse abilities of students. This study recommends increasing teacher-parent collaboration, improving learning facilities, and adjusting memorization targets to enhance the effectiveness and inclusivity of the program.